A Basic Interpretive Study of Professional Experiences of African-American Women Who Achieve Career Advancement in Institutions of Higher Education - Gunn, Nicole P. (My University, 2025)
In this basic interpretive study, I investigated the career trajectories and professional roles of five African-American women serving as directors at predominantly white, four-year universities. The research explored their understanding of departmental leadership, the strategies they employed to advance within their institutions, and the specific social challenges they encountered. This study contributes to the limited academic literature on African-American female directors by focusing on how their experiences influence their approaches to leadership and professional advancement. Four key themes emerged from the data: domestication of the professional space; influence of family and racial beliefs on leadership; marginalization; and navigating the work environment. The findings suggest that African-American female directors bring valuable leadership attributes that benefit their departments and may facilitate the transition of new African-American students into predominantly white institutions. The study demonstrates how these directors' perspectives on race and gender roles shape their career trajectories and professional practices, and outlines potential directions for further research in the field of higher education leadership.
Keywords: Education, Higher; African Americans--Study and teaching (Higher); Women's studies; Dissertations, Academic--United States; African American women; Educational leadership; Universities and colleges—Administration; Educational equalization